Paham Masyarakat Nusantara terhadap Relasi Agama dan Budaya Perspektif Metodologi Al-Ghazali - Muhamad Ramdani Khoirul Anam; Radea Yuli A Hambali (Gunung Djati Conference Series, 2023)
This study aims to discuss the Al-Ghazali Methodology in reviewing the understanding of society in the archipelago towards religious and cultural relations. The research method used is a qualitative type through literature study. The results and discussion of this study is that there is Al-Ghazali's methodology in reviewing the understanding of the people of the archipelago. The culture of the people of the archipelago in reviewing religious and cultural norms is very intolerant so that it makes individuals in society very fanatical, the diversity of understandings and also culture is one of the reasons this research was made. With Al-ghazali's thoughts regarding morality to address this matter, it is a form of boxing for the community so that intolerant and fanatical forms do not recur in the reality of the archipelago.